Partial rescue of mucopolysaccharidosis type VII mice with a lifelong engraftment of allogeneic stem cells in utero. (February 2015) - Ihara, Norimasa; Akihiro, Umezawa; Onami, Naoko; Tsumura, Hideki; Inoue, Eisuke; Hayashi, Satoshi; Sago, Haruhiko; Mizutani, Shuki
Abstract In utero hematopoietic cell transplantation (IUHCT) has been performed in Mucopolysaccharidosis Type VII (MPSVII) mice, but a lifelong engraftment of allogeneic donor cells has not been achieved. In this study, we sought to confirm a lifelong engraftment of allogeneic donor cells immunologically matched to the mother and to achieve partial rescue of phenotypes in the original MPSVII strain through IUHCT by intravenous injection. We performed in vitro fertilization in a MPSVII murine model and transferred affected embryos to ICR/B6‐GFP surrogate mothers in cases where fetuses receiving IUHCT were all homozygous. Lineage‐depleted cells from ICR/B6‐GFP mice were injected intravenously at E14.5. Chimerism was confirmed by flow cytometry at 4 weeks after birth, and β‐glucuronidase activity in serum and several phenotypes were assessed at 8 weeks of age or later. Donor cells in chimeric mice from ICR/B6‐GFP mothers were detected at death, and were confirmed in several tissues including the brains of sacrificed chimeric mice. Although the serum enzyme activity of chimeric mice was extremely low, the engraftment rate of donor cells correlated with enzyme activity. Furthermore, improvement of bone structure and rescue of reproductive ability were confirmed in our limited preclinical study. We confirmed the lifelong engraftment of donor cells in an original immunocompetent MPSVII murine model using intravenous IUHCT with cells immunologically matched to the mother without myeloablation, and the improvement of several phenotypes.